POLA BERFIKIR INOVASI UMKM SINDANG HEULA: KERAMAHAN LOKAL MASYARAKAT KABUPATEN SERANG BANTEN - Ade Manggala Hardianto; Suheli Suheli; Cepi Nurhayana; Sam Sidik; Yusuf Wibisono; Ana Maulana Mus; Eva Muti’ah; Basrowi Basrowi; Bambang Dwi Suseno (Gapenas Publisher, 2023)
Covid-19 has had an impact on various fields, especially rural MSMEs or middle to lower MSMEs. Many merchants and craftsmen failed to continue their business due to the pandemic. Various efforts have been made to improve community efforts but have not yielded satisfactory results. There needs to be an increase in the ability of the community both in the field of marketing and product innovation in order to compete with other products. The purpose of this community service is to find out the extent of the influence of socialization of MSME product development on improving public opinion. The methods used in community service are socialization and practice. Data collection techniques through pre-test and post-test. The result of this community service is a significant increase in public knowledge about product innovation to increase people's income